Administración del riesgo operacional en Colombia. Estado de la implementación del SARO en el sector bancario (2019)
The growing importance of operational risk has influenced control systems structures and the regulation of international financial markets. This article assesses the current state of the implementation of the Operational Risk Management System (ORMS) established under the “Circular 048” by the Financial Superintendency of Colombia at the Colombian banking sector. The assessment comprises tree subjects from the bank’s viewpoint: the motivation and commitment towards the operational risk, the implementation process and contents of “Circular 048”, and the practical problems regarding the implementation process of the regulation. These issues are analyzed based on the results of a survey to all local banks and an interview with the Financial Superintendency of Colombia.